Novel high-strength light building material and production method thereof

Through the composition and process of new high-strength lightweight building materials, the problem that existing building materials cannot meet the lightweight performance needs is solved, and the high compressive strength and lightweight performance of the material are optimized, which is suitable for the high-strength, lightweight and durable needs of modern buildings.

CN119613045APending Publication Date: 2025-03-14ANHUI HUALING CONSTR ENG GRP CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411795591.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-09
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

While existing building materials improve strength and load-bearing capacity, they cannot meet the needs of modern buildings for lightweight performance, resulting in increased material density, reduced construction efficiency and waste of resources.

Method used

A new high-strength lightweight building material is adopted, whose composition includes substrate, binder, reinforcement material, ceramic microbeads, polymer modifiers, fillers, hydrophobic agents, retarders and anti-cracking agents. Through reasonable proportioning and process treatment, the pore distribution and interface bonding properties of the material are optimized.

Benefits of technology

The high compressive strength and lightweight properties of the material are optimized, the toughness and crack resistance of the material are improved, the density is reduced, and the demand for high strength, lightweight and durability of modern buildings is met.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention relates to the technical field of building materials, and discloses a novel high-strength lightweight building material and a production method thereof, the novel high-strength lightweight building material comprises the following components by mass: 75-100 parts of a base material; 50 to 80 parts of a binder; 10 to 30 parts of a reinforcing material; 10 to 20 parts of ceramic microbeads; 8 to 15 parts of a polymer modifier; 10 to 25 parts of filler; 2-5 parts of a water repellent; 1 to 5 parts of a retarder; and 2-8 parts of an anti-cracking agent. Through the hollow structure of the ceramic microbeads, the overall density of the material can be remarkably reduced, meanwhile, the rigid shell can provide excellent compression resistance, pore distribution of the material is effectively optimized, the material is kept light without sacrificing strength, a flexible network is formed through the polymer modifier, the toughness and crack resistance of the material can be remarkably improved, and the service life of the material is prolonged. The interface bonding force between particles is enhanced, and the compactness and the strength of the material are further improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of building materials, in particular to a novel high-strength lightweight building material and a production method thereof. Background Art

[0002] Building materials are an important part of construction projects and building structures, and their performance directly affects the service life and overall quality of buildings. In modern construction projects, with the growing demand for energy conservation and emission reduction, efficient construction, and high-performance building materials, the development of building materials continues to move towards high strength, light weight, and multifunctionality. High-strength materials can improve the bearing capacity of building structures and extend their service life; lightweight materials can help reduce the weight of buildings, reduce infrastructure costs, and improve construction convenience.

[0003] In the prior art, when building materials are used, in order to ensure the high strength and bearing capacity of the overall structure, high-density fillers and aggregates are usually used as the main components. However, although this design method can improve the bearing capacity and compressive resistance of the material, it inevitably increases the density of the material significantly, resulting in its lightweight performance being unable to meet the needs of modern construction to reduce the weight of the building, improve construction efficiency and save resources. Summary of the invention

[0004] In view of the shortcomings of the prior art, the present invention provides a new type of high-strength lightweight building material and a production method thereof, which solves the problem that in the prior art, high-density fillers and aggregates are used as main components to ensure structural strength and bearing capacity, but this results in the inability to meet lightweight performance requirements.

[0005] To achieve the above objectives, the present invention is implemented through the following technical solutions: A new type of high-strength lightweight building material, comprising the following components by mass:

[0006] Base material: 75-100 parts;

[0007] Binder: 50-80 parts;

[0008] Reinforcement material: 10-30 parts;

[0009] Ceramic micro beads: 10-20 parts;

[0010] Polymer modifier: 8-15 parts;

[0011] Filler: 10-25 parts;

[0012] Water repellent: 2-5 parts;

[0013] Retarder: 1-5 parts;

[0014] Anti-cracking agent: 2 to 8 parts.

[0015] Preferably, the substrate comprises expanded perlite or expanded vitrified microspheres.

[0016] Preferably, the binder is silicate cement, and the reinforcing material is one of glass fiber, carbon fiber or basalt fiber.

[0017] Preferably, the ceramic microbeads are hollow ceramic microparticles, and the diameter of the ceramic microbeads is 60 to 100 μm.

[0018] Preferably, the water repellent is one of silane / siloxane water repellent or paraffin-based emulsion water repellent, the retarder is one of citric acid or lignin sulfonate, and the anti-cracking agent is one of polypropylene fiber or sulphoaluminate expansion agent.

[0019] Preferably, the filler is a combination of building sand and fly ash, and the building sand accounts for 50% to 70% of the total amount of the filler.

[0020] Preferably, the polymer modifier includes one of polyvinyl alcohol, epoxy resin emulsion or polyacrylate.

[0021] A method for producing a novel high-strength lightweight building material comprises the following steps:

[0022] a. Raw material pretreatment:

[0023] The substrate is dried in advance, the surface of the ceramic beads is cleaned in advance, the reinforcing material is chopped short, and the filler is screened and cleaned to ensure that there are no impurities;

[0024] b. Basic Mixing:

[0025] Add the base material, binder, reinforcing material and filler into the mixing device in sequence and then stir them evenly;

[0026] c. Modifier mixing:

[0027] The polymer modifier, the water repellent, the retarder and the anti-cracking agent are gradually added into the base mixture and mixed until the liquid components are uniformly attached to the surface of the solid particles;

[0028] d. Drying and crushing:

[0029] The mixture obtained in step c is placed in a drying process, and after drying, it is crushed to obtain a new type of high-strength and lightweight building material.

[0030] Preferably, in step a:

[0031] The substrate is dried using a drum dryer, and the drying temperature of the drum dryer is 50 to 70°C and the drying time is 4 to 6 hours;

[0032] The ceramic microbeads are cleaned using an airflow cleaning device, wherein the airflow pressure of the airflow cleaning device is 0.4-0.8MPa, the airflow velocity is 10-20m / s, the cleaning time is 1-2min, the equipment temperature is 45-50°C, and the cleaning batch is 18-20kg / batch;

[0033] Use a short cutter to cut the reinforcement material to a length of 2 to 5 mm;

[0034] In step b:

[0035] A twin-shaft horizontal mixer is used for stirring at a speed of 300 to 400 r / min for 5 to 8 minutes to form a uniform dry mix.

[0036] Preferably, in step c:

[0037] The mixing speed was increased to 450-500 rpm and the stirring time was 3-5 min.

[0038] In step d:

[0039] The mixture is dried using a fluidized bed dryer, and the inlet temperature of the fluidized bed dryer is 70-80°C, the outlet temperature is 40-45°C, the air flow velocity is 0.5-0.8 m / s, and the drying time is 0.5-1h;

[0040] The dried mixture is pulverized to a particle size of 100 to 200 μm.

[0041] The present invention provides a new type of high-strength lightweight building material and a production method thereof. It has the following beneficial effects:

[0042] 1. The hollow structure of ceramic microbeads can significantly reduce the overall density of the material. At the same time, its rigid shell can provide excellent compressive resistance and effectively optimize the pore distribution of the material, so that it remains light without sacrificing strength. The flexible network formed by polymer modifiers can significantly improve the toughness and crack resistance of the material, enhance the interfacial adhesion between particles, and further improve the density and strength of the material.

[0043] 2. The present invention combines the rigid support provided by ceramic microspheres with the flexible network formed by polymer modifiers, so that the material achieves optimization between compressive strength and toughness. At the same time, the polymer modifier uniformly coats the surface of the ceramic microspheres, which not only improves the pore structure distribution, but also enhances the interfacial bonding performance between the microspheres and the surrounding substrate, improves the overall strength and durability of the material, and always extends the service life of the material to meet the needs of lightweight, high-strength and durable construction applications. DETAILED DESCRIPTION

[0044] The following will be combined with the specification of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0045] In order to better understand the present invention, the above contents are described in detail below in conjunction with specific embodiments.

[0046] The embodiment of the present invention provides a novel high-strength lightweight building material, comprising the following components by mass:

[0047] Base material: 75-100 parts;

[0048] Binder: 50-80 parts;

[0049] Reinforcement material: 10-30 parts;

[0050] Ceramic micro beads: 10-20 parts;

[0051] Polymer modifier: 8-15 parts;

[0052] Filler: 10-25 parts;

[0053] Water repellent: 2-5 parts;

[0054] Retarder: 1-5 parts;

[0055] Anti-cracking agent: 2 to 8 parts.

[0056] The substrate includes expanded perlite or expanded vitrified microspheres;

[0057] in:

[0058] Expanded perlite is a volcanic glass mineral that has been expanded at high temperature. Its structure is honeycomb-like and microporous, with an extremely low density (0.1-0.2g / cm 3 ) and good thermal insulation performance, which can significantly reduce the overall density of the material and achieve the goal of lightweight. At the same time, due to its porous structure, expanded perlite can provide good sound insulation and adsorption capacity in the material, and is suitable for building materials that require light weight, sound insulation and thermal insulation performance. In addition, expanded perlite has high chemical stability, corrosion resistance, and aging resistance, which can enhance the service life of the material in harsh environments;

[0059] Expanded vitrified microspheres are hollow spherical particles formed by vitrification treatment, which have higher strength and thermal stability. Its density is slightly higher than that of expanded perlite, but it is still a lightweight material (0.2-0.4g / cm 3), suitable for construction applications that require higher strength and durability. The surface of expanded vitrified microspheres is dense and smooth, with low water absorption, which can significantly improve the water resistance of the material and reduce the shrinkage and cracking of the material in subsequent construction. At the same time, its regular spherical structure can improve fluidity in the mixture, making construction more convenient and the material forming more uniform.

[0060] The binder is silicate cement, and the reinforcing material is set to be one of glass fiber, carbon fiber or basalt fiber;

[0061] in:

[0062] By using silicate cement as a binder, a large amount of calcium sulfonate and calcium silicate hydrate are generated during the hydration process of silicate cement. These products can form high-strength bonding bridges between particles, significantly improving the overall strength and density of the material and ensuring the firm bonding of the components. The hydration and hardening products of silicate cement have high compressive strength, which makes the building materials have excellent rigidity and durability when subjected to external loads, and are suitable for building structures in high-load scenarios. At the same time, silicate cement has good durability, and its solidified products are not easily corroded by acids, alkalis or other chemicals under normal conditions, which can extend the service life of building materials. In addition, its high impermeability can effectively prevent the penetration of water or other corrosive substances, further improving the weather resistance of the material. And silicate cement has good plasticity and suitable setting time, which can enable the material to maintain good processing performance during the construction process. At the same time, its rapid hardening characteristics meet the needs of rapid construction and high-efficiency engineering:

[0063] By providing the reinforcement material as one of glass fiber, carbon fiber or basalt fiber, wherein:

[0064] Glass fiber has excellent tensile properties, which can effectively prevent the material from breaking or deforming when subjected to stress. Glass fiber also has strong tolerance to acids, alkalis and most chemicals, and can maintain stable performance in harsh environments. At the same time, the glass fiber production process is mature and low-cost, making it an economical and efficient reinforcement material suitable for large-scale construction material production;

[0065] Carbon fiber has higher tensile strength and modulus than steel, which can significantly enhance the material's load-bearing capacity and is particularly suitable for building structures with high strength requirements. In addition, carbon fiber has an extremely low density, which can significantly increase the strength while maintaining the material's lightweight properties. At the same time, carbon fiber has excellent stability in high temperature, humid and corrosive environments, and is suitable for building applications that are exposed to harsh conditions for a long time.

[0066] Basalt fiber can withstand high temperatures of up to 700°C and has better thermal stability than glass fiber, making it an ideal choice for fire-resistant building materials. Basalt fiber also has high strength and high toughness, which can improve the material's crack resistance and impact resistance. At the same time, basalt fiber is made by melting and drawing natural basalt, and no harmful substances are emitted during the production process.

[0067] Ceramic microbeads are hollow ceramic particles with a diameter of 60 to 100 μm.

[0068] By utilizing the low-density structure of hollow ceramic microspheres, the overall density of the material is significantly reduced, making the building materials lighter while having sufficient strength, effectively reducing construction loads and reducing transportation costs. Its particle size range of 60 to 100 μm can be evenly distributed in the material, further optimizing the lightweight characteristics of the material. In addition, the hollow structure of the ceramic microspheres provides good compressive resistance through a rigid shell, forming a microscopic support structure inside the material to help improve the overall strength. The diameter range of 60 to 100 μm ensures that it does not significantly affect the pore distribution of the material while providing strength support. At the same time, ceramic microspheres have excellent thermal stability, and their materials have a high melting point and are not easy to deform, and can maintain structural integrity under high temperature environments. Its hollow characteristics can also isolate heat conduction to a certain extent, providing good thermal insulation and fire resistance for building materials. At the same time, the particle size of ceramic microspheres of 60 to 100 μm ensures the uniformity of particle distribution and can form an ordered pore structure inside the material. This structure effectively prevents the strength loss caused by large pores while maintaining lightness, further improving the density and durability of the material. Moreover, the spherical particles of hollow ceramic microspheres have good fluidity during mixing, which can improve the construction adaptability of the material, making it smoother during mold casting or 3D printing, and achieving better molding effects. Therefore, as a lightweight component with a diameter of 60 to 100 μm, hollow ceramic microspheres not only significantly reduce the overall density of building materials, but also improve their compressive strength, thermal stability and construction performance. This specific particle size range achieves an optimized balance between lightness, high strength and uniformity of pore structure, enabling building materials to meet diverse application needs, and is particularly suitable for building scenarios with high requirements for lightweight and fire resistance.

[0069] The water repellent uses one of silane / siloxane water repellent or paraffin-based emulsion water repellent, the retarder uses one of citric acid or lignin sulfonate, and the anti-cracking agent uses one of polypropylene fiber or sulfoaluminate expansion agent.

[0070] Among them, water repellents include:

[0071] Silane / Siloxane Water Repellent

[0072] Silane / siloxane hydrophobic agents penetrate into the pores of building materials and react chemically with the hydroxyl groups on the surface of the materials to generate hydrophobic siloxy groups, thereby forming a durable hydrophobic protective layer inside the materials. This type of hydrophobic agent can significantly reduce water absorption, improve the water resistance of the material, and avoid corrosion and freeze-thaw damage caused by moisture, and is suitable for use in high humidity environments.

[0073] Paraffin-based emulsion water repellent

[0074] The paraffin-based emulsion water repellent forms a continuous film on the surface of the material to prevent water from entering the material, thus achieving a waterproof effect. The water repellent is low-cost and stable in effect. It can improve the durability of the material in a conventional humid environment while avoiding problems such as carbonization and cracking caused by water erosion. It is suitable for scenes with general waterproofing needs.

[0075] Retarders include:

[0076] Citric Acid

[0077] Citric acid is a natural organic retarder that can delay the hydration reaction rate of C3S (tricalcium silicate) and C4AF (tetracalcium aluminoferrate) during cement hydration, prolong the setting time of the material, and provide convenience for construction operations. Citric acid is not only environmentally friendly and non-toxic, but also can maintain a good retarding effect in high temperature environments, avoiding the strength reduction or cracking of cement-based materials due to rapid setting;

[0078] Lignin sulfonate

[0079] Lignin sulfonate is a retarder extracted from lignin. It absorbs on the surface of cement particles to inhibit the hydration reaction rate, thereby prolonging the setting time. It has a certain water-reducing effect, can improve the fluidity and uniformity of the material, and effectively reduce the occurrence of temperature difference cracks in large-volume construction. It is particularly suitable for complex engineering applications of concrete and mortar.

[0080] Anti-cracking agents include:

[0081] Polypropylene fiber

[0082] Polypropylene fibers disperse in the material to form a multi-dimensional reinforcement network, which can significantly improve the tensile strength and toughness of the material, inhibit the generation and expansion of cracks, and effectively prevent cracking caused by plastic shrinkage or shrinkage. In addition, its excellent corrosion resistance and durability are particularly suitable for the crack prevention and control needs of cement-based materials such as concrete and mortar in various environments;

[0083] Sulphoaluminate expansion agent:

[0084] Sulphoaluminate expansive agents generate expansion products (such as ettringite) during the hydration process to compensate for the shrinkage effect of cement-based materials during the hardening stage, thereby preventing cracking. This expansive agent not only improves the material's crack resistance, but also improves its density and impermeability, and is particularly suitable for large-volume concrete and building materials with high crack resistance requirements.

[0085] The filler is a combination of construction sand and fly ash, and the construction sand accounts for 50% to 70% of the total filler; wherein: construction sand and fly ash are used in combination as fillers, and the construction sand is used to provide skeleton support: construction sand, as a coarse-grained material, plays a skeleton role in the material, enhancing the overall rigidity and compressive resistance, and the particle shape of the sand particles makes the mixture have better fluidity during mixing and construction, facilitating uniform distribution and molding, while fly ash, as a fine-grained material, can fill the tiny pores between the construction sand particles, increase the density of the material, and improve its strength and durability. The volcanic ash properties of fly ash react with calcium hydroxide in silicate cement to form secondary gelling products, further improving the material's compressive and flexural properties;

[0086] In addition, construction sand provides macroscopic skeleton support, while fly ash fills the gaps between sand particles. The reasonable ratio of the two (sand accounts for 50% to 70%) ensures the optimal balance between the strength and density of the material. The sand particles enhance the fluidity and formability of the mixture, while the fine particles of fly ash can reduce the shrinkage and cracking problems of the material, and improve the construction adaptability and molding effect. At the same time, the active characteristics of fly ash are combined with the stability of construction sand to make the material more resistant to chemical erosion, and have good impermeability and frost resistance, suitable for a variety of complex environments. Therefore, the combination of construction sand and fly ash not only provides high strength, density and durability, but also improves construction performance and reduces material costs. The proportion of sand accounting for 50% to 70% of the total filler not only ensures sufficient skeleton support, but also optimizes the pore structure and mechanical properties through the filling and activity of fly ash, so that the material can be widely used in high-performance building application scenarios.

[0087] The polymer modifier includes one of polyvinyl alcohol, epoxy resin emulsion or polyacrylate;

[0088] The hydroxyl groups in the molecular structure of polyvinyl alcohol can form hydrogen bonds with inorganic binders (such as cement), significantly enhancing the bonding performance between particles and improving the overall strength and density of the material. In addition, a flexible network structure is formed during the curing process, which can absorb and disperse stress, reduce crack propagation, and significantly improve crack resistance. At the same time, the coating effect of polyvinyl alcohol on the particle surface enhances the material's water resistance and impermeability, extending the material's service life.

[0089] Epoxy resin emulsion forms a high-strength cross-linked network during the curing process, which greatly improves the material's compression, tension and flexural properties. Epoxy resin emulsion has excellent tolerance to acids, alkalis and other chemicals, and is suitable for construction scenes in harsh chemical environments. Epoxy resin emulsion also has good lubrication properties, which can improve the fluidity and uniformity of the material during the construction process.

[0090] The elastic film formed by polyacrylate in the material has good flexibility and adhesion, which significantly improves the material's crack resistance and impact resistance, and has strong resistance to ultraviolet rays and oxidation, making the material less prone to aging in long-term exposure environments. At the same time, as a water-based polymer, polyacrylate is more environmentally friendly during production and use.

[0091] Therefore, polymer modifiers significantly enhance the bonding force, crack resistance and flexibility of materials through chemical or physical crosslinking with inorganic binders (such as Portland cement). Regardless of which polyvinyl alcohol, epoxy resin emulsion or polyacrylate is selected, the mechanical properties and durability of building materials can be greatly improved. At the same time, depending on the specific application requirements, polyvinyl alcohol can be selected to improve crack resistance and water resistance, epoxy resin emulsion to enhance strength and corrosion resistance, or polyacrylate to improve flexibility and weather resistance, thereby achieving comprehensive optimization of the performance of lightweight building materials.

[0092] The production method of the above material comprises the following steps:

[0093] a. Raw material pretreatment:

[0094] The substrate is dried in advance, the surface of the ceramic beads is cleaned in advance, the reinforcing material is chopped short, and the filler is screened and cleaned to ensure that there are no impurities;

[0095] b. Basic Mixing:

[0096] Add the base material, binder, reinforcing material and filler into the mixing device in sequence and then stir them evenly;

[0097] c. Modifier mixing:

[0098] The polymer modifier, the water repellent, the retarder and the anti-cracking agent are gradually added into the base mixture and mixed until the liquid components are uniformly attached to the surface of the solid particles;

[0099] d. Drying and crushing:

[0100] The mixture obtained in step c is placed in a drying process, and after drying, it is crushed to obtain a new type of high-strength and lightweight building material.

[0101] In step a:

[0102] The substrate is dried using a drum dryer, and the drying temperature of the drum dryer is 50 to 70°C and the drying time is 4 to 6 hours;

[0103] The ceramic microbeads are cleaned using an airflow cleaning device, wherein the airflow pressure of the airflow cleaning device is 0.4-0.8MPa, the airflow velocity is 10-20m / s, the cleaning time is 1-2min, the equipment temperature is 45-50°C, and the cleaning batch is 18-20kg / batch;

[0104] Use a short cutter to cut the reinforcement material to a length of 2 to 5 mm;

[0105] In step b:

[0106] A twin-shaft horizontal mixer is used for stirring at a speed of 300 to 400 r / min for 5 to 8 minutes to form a uniform dry mix.

[0107] In step c:

[0108] The mixing speed was increased to 450-500 rpm and the stirring time was 3-5 min.

[0109] In step d:

[0110] The mixture is dried using a fluidized bed dryer, and the inlet temperature of the fluidized bed dryer is 70-80°C, the outlet temperature is 40-45°C, the air flow velocity is 0.5-0.8 m / s, and the drying time is 0.5-1h;

[0111] The dried mixture is pulverized to a particle size of 100 to 200 μm.

[0112] Embodiment 1

[0113] 1. Experimental Design and Analysis

[0114] Purpose

[0115] Verify the effects of different ratios of ceramic microspheres and polymer modifiers on the performance of high-strength and lightweight building materials.

[0116] 2. According to the content and scope of the embodiment, nine experimental groups were designed. Instructions for setting up the experimental groups:

[0117] Control variable principle

[0118] Only the ratio of ceramic microbeads and polymer modifier was adjusted, and the other components remained unchanged to ensure that the experimental results only reflected the effects of these two components on the material properties.

[0119] Component ratio range

[0120] According to the range values ​​given in the examples, the ceramic microbeads are 10 to 20 parts, and the polymer modifier is 8 to 15 parts.

[0121] When designing the experimental group, the proportions within the range and out of the range (above and below) are selected for analysis.

[0122] Experimental group settings

[0123] Set up 9 experimental groups, including:

[0124] Group 1: The ratios of ceramic microbeads and polymer modifiers are within the range, serving as the control group, specifically:

[0125] Base material (expanded perlite): 90 parts;

[0126] Binder (Portland cement): 65 parts;

[0127] Reinforcement material (glass fiber): 20 parts;

[0128] Ceramic micro beads: 15 parts;

[0129] Polymer modifier (polyvinyl alcohol): 10 parts;

[0130] Filler (construction sand and fly ash): 15 parts;

[0131] Water repellent (paraffin-based emulsion water repellent): 3 parts;

[0132] Retarder (lignin sulfonate): 2 parts;

[0133] Anti-cracking agent (sulfoaluminate expansion agent): 5 parts.

[0134] Group 2-9: Test the ratio of the two values ​​above, below, or within or outside the range. The detailed ratio is shown in Table 1:

[0135] Table 1

[0136]

[0137] Table 1 Summary

[0138] Group 1: Ceramic microbeads and polymer modifiers are within the range.

[0139] Group 2: Both ratios were higher than the range value.

[0140] Group 3: Both ratios were below the range.

[0141] Group 4: Ceramic microbeads within the range, polymer modifier above the range.

[0142] Group 5: Ceramic microbeads within the range, polymer modifier below the range.

[0143] Group 6: polymer modifier within the range, ceramic microbeads above the range.

[0144] Group 7: polymer modifier within the range, ceramic microbeads below the range.

[0145] Group 8: polymer modifier is above the range value, ceramic microbeads are below the range value.

[0146] Group 9: polymer modifier below the range, ceramic microbeads above the range.

[0147] 3. Preparation steps:

[0148] Raw material pretreatment

[0149] The substrate (expanded perlite) was dried using a drum dryer at 60°C for 5 hours;

[0150] The ceramic microbeads were cleaned by airflow cleaning equipment with an airflow pressure of 0.7 MPa, an airflow velocity of 15 m / s, and a cleaning time of 1.4 minutes;

[0151] The reinforcing material (glass fiber) was cut to a length of 4 mm using a chopper;

[0152] The fill material (construction sand and fly ash) is screened to remove impurities.

[0153] Basic Mix

[0154] The base material, binder, reinforcing material and filler were added to a twin-shaft horizontal mixer in sequence and stirred at a speed of 350 r / min for 7 minutes to form a uniform dry mix.

[0155] Modifier Mixing

[0156] The polymer modifier, hydrophobic agent, retarder and anti-cracking agent are made into liquid solutions and gradually added into the dry mixture. The mixture is stirred at a speed of 500 r / min for 5 minutes to ensure that the liquid components are evenly attached to the surface of the solid particles.

[0157] Drying and crushing

[0158] The mixture was dried using a fluidized bed dryer with an inlet temperature of 80°C, an outlet temperature of 40°C, an air flow velocity of 0.7 m / s, and a drying time of 0.8 h;

[0159] The dried mixture is crushed into a particle size of 130 μm using a jet mill to prepare a powdered raw material.

[0160] According to the dry powder weight of the test group, the amount of water added was controlled at 22%, based on the total mass of dry powder.

[0161] Mixing equipment: Use a double-shaft horizontal mixer or other suitable equipment to mix the dry powder and water evenly, ensuring that the water distribution is even and there is no dry powder residue in the material. Use a clean, crack-free mold (such as a steel mold or a plastic mold), and apply a layer of mold release agent on the inner surface of the mold to facilitate demolding. Then pour the evenly mixed wet mixture into the mold, and use a vibrating table or hydraulic compactor to vibrate and compact it to eliminate internal bubbles and ensure the density of the molded sample.

[0162] The compaction parameters are:

[0163] Vibration time: 30-60 seconds (depending on the sample size).

[0164] Compacting pressure: 10MPa (applicable to hydraulic compactor).

[0165] After forming, the sample was left to stand at room temperature (20±2°C) for 6 hours to allow for initial setting.

[0166] After the initial setting is completed, the sample is removed from the mold to avoid disturbing and damaging the sample surface.

[0167] Curing equipment: Use a constant temperature and humidity curing box or a standard curing room.

[0168] Maintenance conditions:

[0169] Temperature: 20±2℃;

[0170] Relative humidity: ≥90%.

[0171] Curing time: Static curing for 28 days to ensure complete hydration reaction inside the material.

[0172] Finished product sample preparation

[0173] Size: Prepare standard cubic samples (such as 50×50×50 mm) for subsequent compressive strength testing.

[0174] Record sample mass: After curing is completed, record the final mass and volume of each set of samples for calculation of density and other performance parameters.

[0175] 5. Strength and quality test

[0176] Compressive strength test

[0177] Equipment: Electronic universal material testing machine;

[0178] Method: According to GB / T 17671-1999 standard, the compressive strength test of the test block with the size of 50×50×50mm after molding was carried out, and the unit is MPa.

[0179] Density test

[0180] Equipment: Density tester (density bottle method);

[0181] Method: Measure the bulk density of the molded sample in g / cm 3 .

[0182] The nine experimental groups were tested and the data were recorded. The detailed data are shown in Table 2.

[0183] Table 2

[0184] Experimental Group Compressive strength(MPa) <![CDATA[Density (g / cm 3 )]]> Group 1 35.0 0.85 Group 2 25.0 0.78 Group 3 15.0 0.95 Group 4 30.0 0.80 Group 5 18.0 0.92 Group 6 28.0 0.75 Group 7 20.0 0.88 Group 8 22.0 0.83 Group 9 26.0 0.77

[0185] Summarize

[0186] The experimental results table records the compressive strength and density of different experimental groups. The differences between the experimental groups are due to the changes in the ratio of ceramic microspheres and polymer modifiers. The following is a detailed analysis of the experimental results of each group:

[0187] Experimental group 1 (control group)

[0188] Component ratio: 15 parts of ceramic microbeads and 10 parts of polymer modifier, both are within the range.

[0189] Performance results: compressive strength 35.0MPa, density 0.85g / cm 3 , which is the best performance among all experimental groups.

[0190] Analysis: The ratio of ceramic microspheres and polymer modifiers achieves a balance between light weight and high strength within a certain range. The hollow structure of ceramic microspheres optimizes the pore distribution, providing light weight and rigid support; the polymer modifier enhances the bonding force and toughness through cross-linking, avoiding the expansion of cracks. The synergistic effect of the two makes the material both light and high-strength, suitable for a variety of construction scenarios.

[0191] Experimental group 2 (both ratios were higher than the range)

[0192] Component ratio: 25 parts of ceramic microbeads and 18 parts of polymer modifier.

[0193] Performance results: compressive strength 25.0MPa, density 0.78g / cm 3 .

[0194] Analysis: Although a high proportion of ceramic microspheres further reduces the density, the excessive amount of hollow particles weakens the overall density of the material, resulting in a decrease in compressive strength. In addition, the excessive increase in polymer modifiers may lead to uneven distribution of the binder at the interface, weakening the strength of the material. This shows that the ratio of the two exceeding the range value will destroy the balance between the lightness and strength of the material.

[0195] Experimental group 3 (both ratios were lower than the range)

[0196] Component ratio: 5 parts of ceramic microbeads and 5 parts of polymer modifier.

[0197] Performance results: compressive strength 15.0MPa, density 0.95g / cm 3 .

[0198] Analysis: Insufficient content of ceramic microspheres leads to a significant decrease in lightweight performance and a significant increase in material density. At the same time, insufficient polymer modifiers lead to a lack of toughness and adhesion at the bonding interface, and reduced crack resistance. This indicates that the ratio below the range value cannot meet the requirements of lightweight and high-strength performance.

[0199] Experimental Group 4 (ceramic microbeads within the range, polymer modifier above the range)

[0200] Component ratio: 15 parts of ceramic microbeads and 18 parts of polymer modifier.

[0201] Performance results: compressive strength 30.0MPa, density 0.80g / cm 3 .

[0202] Analysis: The reasonable content of ceramic microspheres provides good lightweight performance, but the excessive amount of polymer modifier may lead to a decrease in the compatibility of the material and affect the compressive strength. The proportion of polymer modifier should be kept within the range to achieve optimal performance.

[0203] Experimental Group 5 (ceramic microbeads within the range, polymer modifier below the range)

[0204] Component ratio: 15 parts of ceramic microbeads and 5 parts of polymer modifier.

[0205] Performance results: compressive strength 18.0MPa, density 0.92g / cm 3 .

[0206] Analysis: The content of ceramic microspheres is moderate and the density is within a reasonable range, but the lack of polymer modifiers leads to a decrease in the toughness and crack resistance of the material, and the crack propagation cannot be effectively controlled, resulting in low compressive strength. This shows that polymer modifiers play a key role in improving the strength of materials.

[0207] Experimental Group 6 (Polymer modifier within the range, ceramic microbeads above the range)

[0208] Component ratio: 25 parts of ceramic microbeads and 10 parts of polymer modifier.

[0209] Performance results: compressive strength 28.0MPa, density 0.75g / cm 3 .

[0210] Analysis: Excessive ceramic microspheres significantly reduce the density, but at the same time destroy the compactness and rigid support of the material, causing a decrease in compressive strength. Although the polymer modifier content is moderate, it cannot completely make up for the loss of mechanical properties caused by excessive ceramic microspheres.

[0211] Experimental Group 7 (Polymer modifier within the range, ceramic microbeads below the range)

[0212] Component ratio: 5 parts of ceramic microbeads and 10 parts of polymer modifier.

[0213] Performance results: compressive strength 20.0MPa, density 0.88g / cm 3 .

[0214] Analysis: The lack of ceramic microspheres leads to a decrease in lightweight performance, high density, and insufficient support from hollow particles, which affects the overall strength of the material. The polymer modifier provides bonding within a reasonable range, but is not enough to make up for the defects caused by the insufficient proportion of lightweight particles.

[0215] Experimental Group 8 (Polymer modifier is above the range value, ceramic microbeads are below the range value)

[0216] Component ratio: 5 parts of ceramic microbeads and 18 parts of polymer modifier.

[0217] Performance results: compressive strength 22.0MPa, density 0.83g / cm 3 .

[0218] Analysis: Although the excessive amount of polymer modifier improves the toughness of the material, the lack of ceramic microbeads causes the loss of lightweight performance, the density is too high, and the proportion of hollow particles is too low, resulting in the failure to fully exert the mechanical properties of the material.

[0219] Experimental Group 9 (Polymer modifier below the range, ceramic microbeads above the range)

[0220] Component ratio: 25 parts of ceramic microbeads and 5 parts of polymer modifier.

[0221] Performance results: compressive strength 26.0MPa, density 0.77g / cm 3 .

[0222] Analysis: Although the excess ceramic microspheres reduce the density, the lack of polymer modifiers leads to insufficient bonding, affecting the overall compressive performance. The strength and toughness of the material cannot be effectively combined.

[0223] Summary of the advantages of experimental group 1

[0224] The ratio of ceramic microbeads to polymer modifier in experimental group 1 (15 parts and 10 parts) was within the range, and the reasonable ratio achieved the following advantages:

[0225] High compressive strength: Hollow ceramic microspheres provide lightness and rigid support, and polymer modifiers enhance adhesion and toughness. The synergistic effect of the two effectively improves the compressive performance to 35.0MPa.

[0226] Excellent lightweight performance: The moderate proportion of ceramic microbeads ensures the lightweight characteristics of the material, and the density is controlled at 0.85g / cm 3 , taking into account both construction adaptability and material strength.

[0227] Stability and balance: The ratio of the two optimizes the pore structure and interface bonding performance of the material, achieving a balance between light weight and high strength, which is significantly better than other experimental groups.

[0228] Conclusion: The component ratio of experimental group 1 achieved the best balance between compressive strength and lightweight performance, verifying the key role of reasonable ratio of ceramic microspheres and polymer modifiers in optimizing the performance of building materials, and is suitable for a variety of building application scenarios.

[0229] Embodiment 2

[0230] 1. Purpose of the experiment

[0231] The effects of ceramic microspheres and polymer modifiers on building materials (especially concrete performance) were verified, and the changes in compressive strength and density were analyzed by comparing the experimental group with multiple control groups to further verify the synergistic effect of ceramic microspheres and polymer modifiers.

[0232] 2. Experimental and control group settings

[0233] Experimental group (experimental group 1)

[0234] Formula: 90 parts of base material (expanded perlite), 65 parts of binder (Portland cement), 20 parts of reinforcing material (glass fiber), 15 parts of ceramic microspheres, 10 parts of polymer modifier, 15 parts of filler (building sand and fly ash), 3 parts of water repellent, 2 parts of retarder, and 5 parts of anti-cracking agent.

[0235] Control group 1 (ordinary concrete)

[0236] Formula: 300 parts of cement, 600 parts of building sand, 1200 parts of crushed stone, 160 parts of water (standard formula for ordinary concrete, without ceramic microspheres and polymer modifiers).

[0237] Control group 2 (ordinary concrete + ceramic microspheres)

[0238] Formula: Based on control group 1, part of the sand was replaced (90% of sand + 10% of ceramic beads).

[0239] Control group 3 (ordinary concrete + polymer modifier)

[0240] Formula: Based on control group 1, add polymer modifier (5% of cement amount).

[0241] Control group 4 (ordinary concrete + ceramic microspheres + polymer modifier)

[0242] Formula: Based on control group 1, part of the sand was replaced (90% of sand + 10% of ceramic beads), and a polymer modifier (5% of the cement amount) was added.

[0243] 3. Sample preparation and testing steps

[0244] Raw material preparation

[0245] Experimental group: The raw materials were prepared according to the steps in Example 1, including cleaning of ceramic microspheres, drying of substrates, chopping of reinforcing materials, screening of fillers, and uniform mixing and molding operations.

[0246] Control group 1-4: Each component was weighed according to the standard method of ordinary concrete, and ceramic microspheres and / or polymer modifiers were added according to the settings, and added to the mixer in sequence and stirred until uniform.

[0247] Molding steps

[0248] The uniformly mixed materials were injected into standard cubic molds (size: 50×50×50mm), respectively, and the exhaust was vibrated and the surface was scraped flat.

[0249] Maintenance steps

[0250] Place the molded samples in a constant temperature and humidity curing box at 20±2℃ and humidity above 90% for 28 days.

[0251] 4. Test steps

[0252] Compressive strength test

[0253] Equipment: Electronic universal material testing machine;

[0254] Method: According to GB / T 17671-1999 standard test, the sample is placed on the equipment and vertical pressure is applied, and the maximum load at failure is recorded (unit: MPa).

[0255] Density test

[0256] Equipment: Density tester (density bottle method);

[0257] Method: Measure the volume and mass of the sample after curing and calculate the density (unit: g / cm 3 ).

[0258] The experimental results and analysis are shown in Table 3.

[0259] Table 3

[0260]

[0261] 5. Results Analysis

[0262] Experimental group (ceramic microbeads + polymer modifier)

[0263] Performance advantages: Highest compressive strength (35.0MPa), lowest density (0.85g / cm 3 ).

[0264] Analysis of the cause: Ceramic microbeads significantly reduce the density and provide good rigid support; polymer modifiers enhance the bonding and toughness between particles. The synergistic effect of the two optimizes the pore distribution and significantly improves the strength and lightweight performance.

[0265] Control group 1 (ordinary concrete)

[0266] Performance characteristics: compressive strength 30.0MPa, highest density (2.35g / cm 3 ).

[0267] Analysis of the cause: The high density of ordinary concrete comes from the rigid filling of sand and gravel. Although it has high compressive strength, its lightweight performance is obviously insufficient.

[0268] Control group 2 (ordinary concrete + ceramic microspheres)

[0269] Performance changes: Density reduced to 2.10g / cm 3 , but the compressive strength dropped to 25.0MPa.

[0270] Cause analysis: After ceramic microbeads replaced part of the sand, the lightweight performance was improved, but due to the lack of polymer modifiers, the bonding force was insufficient, resulting in a decrease in strength.

[0271] Control group 3 (ordinary concrete + polymer modifier)

[0272] Performance changes: The compressive strength increased to 32.0MPa, but the density remained basically unchanged (2.30g / cm3).

[0273] Cause analysis: The polymer modifier enhanced the adhesion and crack resistance, but the absence of ceramic microbeads did not significantly reduce the density.

[0274] Control group 4 (ordinary concrete + ceramic microspheres + polymer modifier)

[0275] Performance changes: compressive strength increased to 33.5MPa, density reduced to 2.05g / cm 3 .

[0276] Cause analysis: The addition of ceramic microbeads reduces the density, and the polymer modifier enhances the adhesion and crack resistance. The synergistic effect of the two improves the performance, but it is not as good as the experimental group because the sand and gravel content of ordinary concrete formula is still relatively high, which affects the further improvement of lightweight performance.

[0277] VI. Conclusion

[0278] Synergy verification

[0279] The compressive strength and lightweight properties of the experimental group were better than those of the control groups 1-4, verifying that the ceramic microbeads and polymer modifiers can significantly optimize material properties under synergistic effects.

[0280] Limitations of a single component

[0281] The results of Control Groups 2 and 3 show that the use of ceramic microbeads or polymer modifiers alone improves lightness or strength properties, respectively, but not both, further emphasizing the necessity of using both in synergy.

[0282] Performance of Control Group 4

[0283] Control group 4, which combines ceramic microbeads and polymer modifiers, showed improved performance, but did not achieve the optimal balance of the experimental groups, indicating that material formulation optimization is critical to maximizing performance.

[0284] Application prospects: The experimental group of materials has both high strength and light weight performance, which is significantly better than ordinary concrete and single modified formula. It is suitable for fields such as high-rise buildings, bridges and lightweight load-bearing components that have strict requirements on both strength and light weight performance.

[0285] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A new type of high-strength lightweight building material, characterized in that: It includes the following components by mass: Base material: 75-100 parts; Binder: 50-80 parts; Reinforcement material: 10-30 parts; Ceramic micro beads: 10-20 parts; Polymer modifier: 8-15 parts; Filler: 10-25 parts; Water repellent: 2-5 parts; Retarder: 1-5 parts; Anti-cracking agent: 2 to 8 parts.

2. A new type of high-strength lightweight building material according to claim 1, characterized in that: The substrate includes expanded perlite or expanded vitrified microspheres.

3. A new type of high-strength lightweight building material according to claim 1, characterized in that: The binder is silicate cement, and the reinforcing material is one of glass fiber, carbon fiber or basalt fiber.

4. A new type of high-strength lightweight building material according to claim 1, characterized in that: The ceramic microbeads are hollow ceramic microparticles, and the diameter of the ceramic microbeads is 60-100 μm.

5. A new type of high-strength lightweight building material according to claim 1, characterized in that: The water repellent is one of silane / siloxane water repellent or paraffin-based emulsion water repellent, the retarder is one of citric acid or lignin sulfonate, and the anti-cracking agent is one of polypropylene fiber or sulphoaluminate expansion agent.

6. A new type of high-strength lightweight building material according to claim 1, characterized in that: The filler is a combination of construction sand and fly ash, and the construction sand accounts for 50% to 70% of the total amount of the filler.

7. A new type of high-strength lightweight building material according to claim 1, characterized in that: The polymer modifier includes one of polyvinyl alcohol, epoxy resin emulsion or polyacrylate.

8. A method for producing a novel high-strength lightweight building material, used for producing a novel high-strength lightweight building material according to any one of claims 1 to 7, characterized in that: The following steps are involved: a. Raw material pretreatment: The substrate is dried in advance, the surface of the ceramic beads is cleaned in advance, the reinforcing material is chopped short, and the filler is screened and cleaned to ensure that there are no impurities; b. Basic Mixing: Add the base material, binder, reinforcing material and filler into the mixing device in sequence and then stir them evenly; c. Modifier mixing: The polymer modifier, the water repellent, the retarder and the anti-cracking agent are gradually added into the base mixture and mixed until the liquid components are uniformly attached to the surface of the solid particles; d. Drying and crushing: The mixture obtained in step c is placed in a drying process, and after drying, it is crushed to obtain a new type of high-strength and lightweight building material.

9. The method for producing a novel high-strength lightweight building material according to claim 8, characterized in that: In step a: The substrate is dried using a drum dryer, and the drying temperature of the drum dryer is 50 to 70°C and the drying time is 4 to 6 hours; The ceramic microbeads are cleaned using an airflow cleaning device, wherein the airflow pressure of the airflow cleaning device is 0.4-0.8MPa, the airflow velocity is 10-20m / s, the cleaning time is 1-2min, the equipment temperature is 45-50°C, and the cleaning batch is 18-20kg / batch; Use a short cutter to cut the reinforcement material to a length of 2 to 5 mm; In step b: A twin-shaft horizontal mixer is used for stirring at a speed of 300 to 400 r / min for 5 to 8 minutes to form a uniform dry mix.

10. The method for producing a novel high-strength lightweight building material according to claim 8, characterized in that: In step c: The mixing speed was increased to 450-500 rpm and the stirring time was 3-5 min. In step d: The mixture is dried using a fluidized bed dryer, and the inlet temperature of the fluidized bed dryer is 70-80°C, the outlet temperature is 40-45°C, the air flow velocity is 0.5-0.8 m / s, and the drying time is 0.5-1h; The dried mixture is pulverized to a particle size of 100 to 200 μm.